MENGENDALIKAN INTENSITAS GLARE MATAHARI MENGGUNAKAN SUN-SHADING SISTEM GESER PADA BUKAAN JENDELA - Choirul Anam; Irwan Sudarisman; Khotibul Umam; Muhammad Fauzan Maulidhani; Muhammad Ridho Satria (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
In the current era, there have been various innovations in the field of design, including in interior design. One innovation that stands out in interior design is the use of sunshading, which is part of the opening element. In the context of a house, increasing the number of openings can increase the penetration of natural light into the room, along with the possible increase in temperature. In addition, the ability to dampen the heat generated by sunlight can also reduce the need for cooling, thus having a positive impact on more efficient energy use. Attention should also be paid to the glare factor, as excessive brightness can affect comfort levels. There are many examples of houses and structures that are close together in an area, but have notable differences in their architectural design. Therefore, the planning of building facades needs to consider the design of sun shading devices that are able to control the intensity of incoming sunlight, apart from its benefits in terms of interior aesthetics, sun shading is also able to create a pleasant visual experience for the eyes and contribute as an aesthetic element in the room.